Letter to Jane Tolmach from Senator Henry M. Jackson - Henry M. Jackson:::::: (1961)
A letter to Jane Tolmach from Senator Henry M. Jackson. The letter thanks Jane for her letter on September 20th the Senator visiting Ventura County.